1994
DOI: 10.1149/1.2059253
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Microroughness Generation on the Silicon Wafer Surface in Buffered Hydrogen Fluoride by a Surfactant Addition

Abstract: In order to prevent microroughness generation on the Si wafer surface in buffered hydrogen fluoride (BHF), the addition of a surfactant to BHF was investigated. It was found that mieroroughness generation on the Si wafer surface in BHF was prevented by adding the several 10 ppm surfactant. Also, the dissolution of Si into BHF from the Si wafer surface was suppressed by adding the surfactant. Microroughness generation was suppressed by lowering the N[-I4F concentration in BHF and the dissolution oi Si depended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…Lober et al [44] reported an attack of poly-Si in BHF and vapor HF. Corrosion of bulk silicon immersed for 24 to 48 hours in BHF can be suppressed by addition of a hydrocarbon anionic surfactant [45].…”
Section: Selectivity Against Siliconmentioning
confidence: 99%
“…Lober et al [44] reported an attack of poly-Si in BHF and vapor HF. Corrosion of bulk silicon immersed for 24 to 48 hours in BHF can be suppressed by addition of a hydrocarbon anionic surfactant [45].…”
Section: Selectivity Against Siliconmentioning
confidence: 99%
“…However, attack by buffered HF on poly-silicon, leading to surface roughening, has been reported under various conditions, and has been correlated with the presence of contaminants, such as metals, as well as the deposition conditions or structure of the poly-silicon 24–27 . Microroughening of single-crystal silicon during immersion in buffered HF solutions for very long times (1–5 days) has also been described 28 . An infrared spectroscopy study of Si (111) surfaces exposed to buffered HF solutions of various p H values showed that the etch rate of these surfaces increased with OH − concentration and suggested that oxidation of the surface Si-H species is an important and probably rate limiting step for etching 29 .…”
Section: Resultsmentioning
confidence: 99%
“… 24–27 Microroughening of single-crystal silicon during immersion in buffered HF solutions for very long times (1–5 days) has also been described. 28 An infrared spectroscopy study of Si (111) surfaces exposed to buffered HF solutions of various p H values showed that the etch rate of these surfaces increased with OH − concentration and suggested that oxidation of the surface Si-H species is an important and probably rate limiting step for etching. 29 It is therefore likely that the device degradation observed here is caused by cyclic oxidation of silicon followed by etching of the resulting oxide.…”
Section: Resultsmentioning
confidence: 99%
“…In HF solution, Si dissolution can occur through direct dissolution reactions: It has been reported [40] that the addition of surfactant in buffered HF etching reduces the Si dissolution because the oxidation process of Si (reactions 4 and 5) is suppressed by the adsorption of the surfactant molecules on the Si surface. Moreover, it is well known that IPA reduces the etching of SiO 2 in HF [41] because the HF dissociation decreases.…”
Section: Ipa Effect On Macetch Processmentioning
confidence: 99%